The Influence of Social Media Communication Created By The Company, Brand Equity, Brand Attitude On The Purchase Intention of Gt.Radial Tire Products - Vendy Wijaya (Social Economics and Ecology International Journal (SEEIJ), 2021)
The Purpose of this research is to find out the effect between Firm-Created Social Media Communication on Brand Equity and Brand Attitude which influence Purchase Intention on GT Radial product. The population of this research is the people whose liked the GT Radial Indonesia Facebook fanpage, which is 51.715 people. The method used for collecting data is using a questionnaire with 396 respondents using the Slovin method. The analysis method used for this research is Structural Equation Modeling (SEM). The purpose for using this method is to help assess the measurement properties and test the proposed theoretical relationships by using a single technique. The research methodology used in this research is Quantitative because it will be measurable and systematic to collect data or information that can be used to achieve the purpose of research. The result is between every variable, they have a significant effect. Except Brand Equity variable didn’t have a significant effect on Purchase Intention and can’t be used as mediation variable. The conclusion of this research is that the variable used for mediating between Firm-Created Social Media Communication and Purchase Intention can be replaced by trust variable.